2017
DOI: 10.1177/1010428317705341
|View full text |Cite
|
Sign up to set email alerts
|

MiR-19a regulates the cell growth and apoptosis of osteosarcoma stem cells by targeting PTEN

Abstract: MicroRNAs are small, endogenous, and non-coding RNAs that play important regulatory roles in multiple biological processes in cancers. Recent evidence has indicated that miR-19a participates in the cancer tumorigenic progression. However, the functional roles of miR-19a in cancer stem cells are still unclear. As the cancer stem cells are considered to be responsible for the tumor recurrence and treatment failure in osteosarcoma, the aim of this study is to investigate the molecular mechanism of miR-19a underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…23,24 They have the potential to regulate various critical biological processes including proliferation, migration and apoptosis of different kind of cancer cells. 25,26 Previous studies have indicated that many miRNAs, such as miR-19a, 27 miR-610, 28 CXCR4 is a well-studied G-protein coupled chemokine receptor and commonly expressed on lots of cell types including osteosarcoma cells. 34 The binding of SDF-1 to CXCR4 results in divergent downstream signaling pathways that mediate cell proliferation, migration and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 They have the potential to regulate various critical biological processes including proliferation, migration and apoptosis of different kind of cancer cells. 25,26 Previous studies have indicated that many miRNAs, such as miR-19a, 27 miR-610, 28 CXCR4 is a well-studied G-protein coupled chemokine receptor and commonly expressed on lots of cell types including osteosarcoma cells. 34 The binding of SDF-1 to CXCR4 results in divergent downstream signaling pathways that mediate cell proliferation, migration and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the present study is the first to provide evidence that PITX1 expression is modulated through miR-19a-3p in GC. miR-19a is frequently overexpressed, promotes cell proliferation and the epithelial to mesenchymal transition, and inhibits cell apoptosis in lung carcinoma [36,37], osteosarcoma stem cells [38], colorectal cancer [39][40][41][42], cell renal cell carcinoma [43], oral squamous cell carcinoma [44], hepatocellular carcinoma cells [45], pancreatic cancer [46], GC [47,48], cholangiocarcinoma [49], breast cancer [50], bladder cancer [51], medulloblastoma [52], and cervical carcinoma [53]. Our findings are consistent with these data because they provide evidence that miR19a is a key regulator of the multistep processes of cancer development.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…To find the target of miR-19a-3p, we used Targetscan, miRanda to predict potential target mRNAs, such as KBTBD8, ZMYND11, targeting PTEN in osteosarcoma stem cells and hepatocellular carcinoma. 12,13 Moreover, we found that the expression levels of PTEN mRNA were obviously up-regulated when overexpressed SLC25A5-AS1 in SGC-7901 and BGC-823 cells ( Figure 7A,B).…”
Section: Slc25a5-as1 Inhibits Cell Growth and Promotes Apoptosis VImentioning
confidence: 94%